Acceleration and fatigue in soccer - Varley, M. C. (2013)
This thesis investigated acceleration in soccer and the ability to improve acceleration capacity using supplementation and a training intervention both separately and in combination. Study one determined the validity and reliability of 5 and 10 Hz global positioning systems (GPS) for measuring instantaneous speed during the acceleration, deceleration and constant speed phase of straight-line running. The criterion measure used to assess GPS validity was instantaneous speed recorded using a tripod-mounted laser. Ten Hz GPS devices were 2-3 times more accurate than 5 Hz when compared to a criterion value for instantaneous speed during tasks completed at a range of speeds (coefficient of variation; 3.1 - 11.3%). Similarly, 10 Hz GPS were up to 6-fold more reliable for measuring instantaneous speed than 5 Hz units (coefficient of variation; 1.9 - 6%). Newer GPS may provide an acceptable tool for the measurement of constant speed, acceleration and deceleration during straight-line running and have sufficient sensitivity for detecting changes in performance in team sport. However, researchers must account for the inherent match-to-match variation reported using these devices.